Tìm hiểu động cơ và chiến lược học tập tiếng Việt của sinh viên Đài Loan trong bối cảnh toàn cầu hóa - Vũ Lê Toàn Khoa, Vũ Lê Toàn Khoa (Tạp chí Giáo dục, 2026)
The increase in trade and investment between Vietnam and Taiwan has led to a growing demand for human resources with proficiency in Vietnamese. In this context, an increasing number of Taiwanese students choose to study Vietnamese in order to expand their employment opportunities after graduation. Using in-depth interviews with 25 students, this study examines Taiwanese students’ motivations for learning Vietnamese and the learning strategies they employ. The findings indicate that learners’ motivations and strategies not only influence their learning outcomes but also pose demands on instructors to adjust instructional content and teaching approaches. The study highlights the need for strengthened collaboration between educational institutions and relevant organizations to develop appropriate learning materials and expand opportunities for Vietnamese language practice.